Grain size constraints on arsenic concentration in shallow wells of Nawalparasi, Nepal (Journal of Nepal Geological Society, 2004)
Occurrence of arsenic in shallow aquifers was studied from the Nawalparasi district in west Nepal. A higher concentration of arsenic was found in the wells from the north as compared to those from the south. The arsenic level in the north reaches a maximum of 694ppb as compared to a value of 27 ppb in the south near the Nepal-India border. The arsenic concentration analyses carried out in selected sites from March to September 2003 indicate a large variation (exceeding 200%) in the north as compared to the central and southern regions. A general increase in grain size from north to south was observed in the well logs. Generally, fine sediments like clay and silt constitute more than 80% of the drilled depth in the north (i.e., at Panchnagar), while the fines are about 32% in the south (i.e., at Bhujawa). This type of grain size distribution is in contrast to the generally observed fining-southwards pattern in the Terai.